The Realization by Foreign Citizens of the Right to Unite in Labor Unions: Problems and Solutions - V. V. Korobchenko; V. A. Safonov (Сибирское юридическое обозрение, 2019)
The article deals with the problem of limiting the possibility of membership of foreign citizens and stateless persons which temporarily staying in the territory of the Russian Federation in the Russian labor unions. Based on the study of legislation and practice of its application the authors note that the protection of the rights of workers by labor unions is called upon to supplement state mechanisms for the protection of citizens’ rights and is optional. Realization of the workers’ interests is practically impossible in the absence of their effective association therefore the restrictions that are established for foreign citizens temporarily staying in Russia and stateless persons with regard to membership in labor unions must be assessed from the point of view of ensuring their interests in the field of labor. Objective justification of the ban for the participation to the Russian labor union for a foreign citizen and a stateless person which temporarily staying in the Russia is the absence of long term communication with the Russian Federation for these persons and the short term nature of their interests in the field of labor. At the same time taking into account the possibility of long time employment to these persons in Russia the authors propose to recognize the right to the participation in the labor union for foreign citizens which are skilled workers and work on the basis of a work permit.